CATALYTIC HYDRODEAROMATIZATION OF MOTOR FUELS AS A METHOD OF PRODUCING ECO-FRIENDLY FUELS - Massenova Alma Tulegenovna,; Kalykberdiyev Maksat Kuatovich,; Sass Alexander Sergeevich,; Kenzin Nail Rashidovich,; Abilmagzhanov Arlan Zainutallaevich,; Kanatbayev Yerlan Temirbekovich,; Kassenova Dlara Shitayevna, (Academic Scientific Journal of Chemistry, 2019)
The aim of the work was to study the process of hydrodearomatization of gasoline fractions and diesel fuels for the production of environmentally friendly fuels with a low content of aromatic hydrocarbons. Hydrogenation of two gasoline fractions of LLP Atyrau Refinery (AR) and LLP Pavlodar Refinery (PR) and two diesel fuels of PA and LLP PetroKazakhstanOilProducts, Shymkent (PKOP) on Rh-Pt/Al2O3 catalyst was studied. The influence of the technological parameters of hydrodearomatization process (pressure 1-5 MPa, temperature 25- 200°C) on the content of benzene and aromatic hydrocarbons was studied. At temperatures of 50-200°C and hydrogen pressures of 2-5 MPa, benzene is completely removed from the fractions, and the amount of aromatic hydrocarbons is reduced by 1.5-2 times. Some operational properties (kinematic viscosity at 20°C, pour point and cloud point, flash point, density at 20°C, iodine number, aromatic hydrocarbon content) of the initial diesel fuels of PA and PKOP and after catalytic treatment were determined. In process of hydrodearomatization all operational indicators were improved and approached the standards for diesel fuel, and the cetane index increased by 1-2 units.